OCCUPATIONAL STRESS AMONG ACADEMIC STAFF OF EKITI STATE UNIVERSITY, ADO-EKITI - Adebiyi, Damilola Ruth (European Scientific Journal, ESJ, 2013)
This study examined occupational stress among Ekiti State university academic staff. The purpose of the study was to investigate the occupation-related stress and also to know the influence of gender, faculty and experience on stress experience in Lecturers. The study employed a descriptive research survey type. The research instrument was titledâ€ Stress Questionnaireâ€. The face and content validity was ascertained by psychologist and Guidance and Counselling experts. A reliability co-efficient of 0.72 was obtained. The population of the study includes all faculties in the university. Samples were selected through stratified sampling technique. Three (3) hypotheses were generated and tested using student t-test and ANOVA at 0.05 level of significance. The findings revealed that gender and years of experience does not influence stress on lecturers, but that stress experiences vary from faculty to faculty.